The Impact of the Time Token Learning Model on the Speaking Skills of Fourth-Grade Students in Madrasah Ibtidaiyah - Munthe, Abdal Rizky; Rambe, Riris Nurkholidah (Institut Agama Islam Daruttaqwa Gresik, 2025)
This study aims to determine the impact of the Time Token learning model on the speaking skills of fourth-grade students at MIN 12 Medan. Speaking skills are one of the essential competencies in Indonesian language learning, requiring structured practice and appropriate teaching methods. This research employed a quantitative approach with a quasi-experimental design of the nonequivalent control group type. The sample consisted of 62 students, divided into two groups: the experimental group using the Time Token model and the control group using conventional learning methods. The research instrument was a speaking skills test assessed based on six aspects: accuracy of pronunciation, intonation, articulation, diction, word structure order, and fluency. Data analysis included normality testing, homogeneity testing, and hypothesis testing using an independent sample t-test. The results showed that the data were normally distributed and homogeneous, and the hypothesis test yielded a significance value of 0.001 < 0.05, indicating a significant difference between the two groups. The average posttest score of the experimental group was 27.06, higher than that of the control group, which was 22.06. These findings demonstrate that the Time Token model is efficacious in improving students’ speaking skills. Therefore, Time Token can be applied as an innovative and interactive learning strategy to develop students’ oral communication abilities.